The Correlation between Ferritin Levels and Glutation (GSH) Levels in Major Beta Thalassemia Patient at dr. Soebandi Jember Hospital - Amalia Nur Zahra; Rini Riyanti; Elly Nurus Sakinah (Journal of Agromedicine and Medical Sciences, 2018)
Repeated blood transfusions in patient with Major Beta Thalassemia leads to iron overload marks by the increased of serum ferritin levels. Free iron caused the change of H2O2 to oxidants by fenton reaction and caused oxidative stress. These oxidants will be counteracted by GSH as antioxidants. The purpose of this study was to investigate the correlation between ferritin levels with GSH in patients with major beta thalassemia in RSD dr. Soebandi hospital Jember. The samples of this study are fifteen (15) patients age 1-18 years who were regularly transfused. Serum ferritin levels were measured by Enzyme-Linked Fluorescent Immuno Assay (ELFA) and plasma GSH levels were measured by Ellman method. Data was analyzed using Pearson correlation test. Serum feritin levels were increased in Major Beta Thalassemia children with average of 3540,46 ± 3925,37 ng/mL. The mean of GSH is 10,46 ± 2,58 µmol. We found significant and negative correlation between serum ferritin and GSH with p value=0,000 and r=-0,951 in Major beta thalassemia patient at RSD dr. Soebandi Jember. Keywords: Thalassemia, Oxidative stress, Feritin, GSH